Shareholders Wealth Effects of Recent Mergers and Acquisitions: the Chinese Experience - Deng, Siyun (2007)
This paper studies the shareholder wealth effects of recent mergers and acquisitions in the Chinese market from 06/2006 to 05/2007. Results show that short-term CARs around the announcement day are significantly positive for both bidding and target companies. However, when cumulating over the 61-day test period, both bidding and target firms suffer significantly negative abnormal return.